Pengaruh Pernikahan Dini Mempengaruhi Kualitas Kehidupan Keluarga Dalam Perspektif Hukum Islam - Ania Nasyira; Faiza Nisrina; Roselia Ariyanti (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Early marriage is a practice that still occurs frequently, especially in Indonesia. Even though in Indonesia there has been legal certainty regarding the age limit for couples who will marry in the form of statutory regulations, one of which is the Marriage Law, in reality the practice of early marriage continues due to various factors, including cultural, economic and lack of education. This research aims to analyze the impact of early marriage on the quality of family life based on the perspective of Islamic law, as well as to examine the views of the Imams of the School regarding early marriage and how the views of these Imams influence the practice of early marriage in Islamic society. By using research methods through a juridical approach and supported by primary and secondary data collection techniques, this research is aimed at providing a comprehensive understanding of the influence of early marriage itself. Based on the research that has been carried out, the results obtained are that early marriage causes more negative impacts than the benefits obtained. These negative impacts include aspects of biological, psychological, social and deviant sexual behavior. Apart from that, there are differences of opinion from Imams regarding the age limit for a person's maturity so that society must really consider the readiness of the child they are going to marry, especially in economic, biological and psychological terms.